Unravelling the structure and function of human hair - Boulos, R.; Eroglu, Ela; Chen, X.; Scaffidi, A.; Edwards, B.; Toster, J.; Raston, C. (2013)
Human hair is transformed into functional nano-dimensional material using a benign choline chloride-urea ionic liquid composite as a deep eutectic melt. The hair and isolated central fibres after treatment with the ionic liquid composite have the ability to immobilise microalgal cells for wastewater treatment and the cuticle cells are effective as templates in coating a sparingly soluble drug molecule which is slowly released at physiological pH. Thus, instead of human hair being a waste, it can be converted to end products with potentially high-end value, with reduced negative impact on the environmental. © 2013 The Royal Society of Chemistry.